London-Smog und Los Angeles-Smog - Kuttler, Wilhelm (ERDKUNDE, 1979)
Low-pressure gradient weather patterns may, depending on the type of immission and the intensity of radiation, cause two different types of smog. The London-smog mostly occurring in the winter months consists of a mixture of gaseous and solid aerosoles as well as of natural fog. The Los Angeles-smog, which is relatively dry, is formed only during sunny sommerdays by photo chemical process. As these two smog types are not exclusively limited to the two cities mentioned above it is suggested that for a large scale geographical application of these two terms a distinction be made according to the respective indicators of the two smog types.